Effects of GHR gene polymorphisms on growth and carcass traits in Zebu and crossbred beef cattle - Curi, Rogerio Abdallah [UNESP]; Palmieri, D. A.; Suguisawa, L.; Ferraz, ALJ; de Oliveira, H. N.; Furlan, L. R.; Silveira, Antonio Carlos [UNESP]; Lopes, C. R. (Elsevier B.V., 2006)
The growth hormone receptor (GHR) is the cell surface receptor for growth hormone (GH) and is required for GH to carry out its effects on target tissues. The objectives of the present study were to estimate the allele and genotype frequencies of the GHR/Alu I gene polymorphism located in the regulatory region in beef cattle belonging to different genetic groups and to determine associations between this polymorphism and growth and carcass traits. Genotyping was performed on 384 animals, including 79 Nellore (Zebu), 30 Canchim (5/8 Charolais+3/8 Zebu), 30 Simmental X Nellore crossbred and 245 Angus x Nellore crossbred cattle. Alleles Alu I(+), Alu I(-) and Alu I(N)-null allele-were evidenced for the GHR/Alu I polymorphism and the frequency of the Alu I(N) allele was significantly higher than the frequency of the Alu I(+) and Alu I(-) alleles in all genetic groups. Genotype Alu I(N/N) of the GHRIAlu I predominated in Nellore animals, while the Alu I(N/+) and Alu I(N/-) predominated in the other genetic groups. In the association studies, traits of interest were analyzed using the General Linear Model (GLM) procedure of the SAS program and least squares means of the genotypes were compared by the Tukey test. Significant associations (P < 0.05) were observed between the Alu I(N/N) genotype of the GHRIAlu I polymorphism and lower weight gain and body weight at slaughter, although a confounding between genotypes and genetic groups may have occurred. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: beef cattle; polymorphisms; GHR; growth; carcass